The story of spying - Jones, Rob Lloyd; Charman, Terry; Tomlins, Karen (London usborne publishing, 2007)
Introduces the history of espionage and discusses World War I spies who were caught and executed, agents who worked with the Resistance in occupied France, the breaking of the Enigma code, espionage during the Cold War, and spy technology
History
Keywords: Children's nonfiction; Espionage History; Espionage History Juvenile literature